Temperature dependences of N2-broadening and shift coefficients in the ν6 perpendicular band of 12CH3D. (September 2015) - Predoi-Cross, A.; Devi, V. Malathy; Sung, K.; Sinyakova, T.; Buldyreva, J.; Benner, D. Chris; Smith, M.A.H.; Mantz, A.W.
Abstract: The temperature-dependences of line broadening and shift parameters for many 12 CH3 D transitions have been determined using six high-resolution, high signal-to-noise ratio, room-temperature CH3 D (98% purity) and CH3 D-N2 spectra recorded with 25 cm path length ( at 0.01 cm −1 unapodized resolution) using the McMath−Pierce FTS located on Kitt Peak, Arizona, and 17 additional high quality, pure CH3 D (99% purity) and CH3 D-N2 spectra recorded between 79 and 296 K with the 20.38 cm path coolable cell (at 0.0056 cm −1 unapodized resolution) with the Bruker 125HR FTS at the Jet Propulsion Laboratory (JPL), Pasadena, California. The spectra have been fitted simultaneously applying a multispectrum nonlinear least-squares technique. In the analysis, the Lorentzian N2 -broadened half-width coefficients and the corresponding pressure-shift coefficients as well as their temperature dependences are extracted for about 400 transitions (0≤ J ″≤19, K ″≤16) in the perpendicular (Δ K =±1) ν6 band. At 296 K, the measured N2 -broadened half-width coefficients range from 0.0209 to 0.0782 cm −1 atm −1 whereas the majority of the associated N2 -induced shift coefficients are negative, and the values are between -0.016 and 0.005 cm −1 atm −1 . The temperature dependence exponents for N2 -broadened half-widths range between 0.264 and 0.924, whereas the temperature dependence coefficients for N2 -induced shifts are between 0 and 0.00011 cm −1 atm −1 K −1 . The N2 -broadened half-width coefficients have been also calculated using a semi-classical approach based on a rigorous treatment of the active molecule as a symmetric top, a model intermolecular potential comprising both short- and long-range interactions, and exact classical trajectories. The role of the various high-order multipoles in the line-broadening at low, middle and high values of the rotational quantum number J ″ has been investigated and the main features of the K -dependences analyzed. The calculations performed for 296, 240 and 190 K have allowed to deduce the half-width temperature-dependence exponents, completing the general comparison of our new experimental results with those which are available in the literature. Highlights: FT-IR study of the line parameters for the ν6 band of CH3 D broadened by N2 . Measurement and modeling of temperature dependences of CH3 D-N2 ν6 line parameters Simultaneous fittings of 23 high-resolution FTS spectra from 296 to 75 K Line mixing retrieved using the off-diagonal relaxation matrix formalism Catalogued all measured line parameters for use in remote sensing applications.